IS EXCHANGE RATE PASS THROUGH EFFECT VALID IN SERBIA? EMPIRICAL TESTING BY USING CO-INTEGRATION TECHNIQUES - Lojanica, Nemanja; Janković, Nenad; Tubić Ćurčić, TIjana (The European Journal of Applied Economics, 2026)
The aim of this paper is to examine whether the exchange rate pass-through effect on prices in Serbia is present. In a small and open economy with a managed floating exchange rate regime, the impact of exchange rate changes on inflation is particularly important. Since this topic has been extensively studied, the contribution of this paper lies in applying several cointegration techniques and analyzing a specific time period for the case of Serbia. The selected time frame is 2007–2021, with monthly data. The research results show that the exchange rate pass-through effect on prices is incomplete. Additionally, it has been found that the effect is more pronounced in the long run and that the strength of the impact depends on the cointegration technique used.
Keywords: exchange rate, inflation, ARDL, case study